Peningkatan Kemampuan Critical Thinking dan Hasil Belajar Siswa Melalui Penerapan Model Problem-Based Learning - Ratna Guntari; Agnes Herlina Dwi Hadiyanti; Yohanes Bruri Kriswanto (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2023)
This research is motivated by the problem of low critical thinking skills and student learning outcomes in the cognitive domain of learning. The purpose of this study was to improve critical thinking skills and learning outcomes in students in grade V. The type of research used was classroom action research (CAR) with 22 fifth grade students at Kanisius Demangan Baru 1 Elementary School as subjects. Data collection techniques used in research are observation, interviews and tests. Data analysis techniques used in this research are quantitative analysis and qualitative analysis. The results of the study showed an increase in critical thinking skills and student learning outcomes in class V SD Kanisius Demangan Baru 1 from the initial conditions with an average of 61% increased in cycle I with an average of 75% and an average of 86% in cycle II. Improved learning outcomes after implementing Problem-based learning for students from the initial average value of 74 to an average of 79 in cycle I and increased again in cycle II to an average of 86 and succeeded in exceeding the KKM. The percentage of completeness also increased significantly from the previous 59% with 13 students who passed to 86% with 19 students.